Trophic ecology of squids in the Benguela Upwelling System assessed through stomach content, fatty acid and stable isotopes analyses in austral spring 2021 - Fatty acid contents of squids - Kira Izabela Kremer; Wilhelm Hagen; Sabrina Dorschner; Anne F Sell (PANGAEA, 2025)
Squids were collected during the research cruise SO285 on RV Sonne in the northern (nBUS) and southern (sBUS) Benguela Upwelling System between September 13 and October 9, 2021 in order to determine their trophic position and nutritional ecology. The cruise was part of the TRAFFIC (Trophic tRAnsfer eFFICiency in the Benguela Current) project. Samples were retrieved from rectangular midwater trawl (RMT) net hauls at 10 stations in the nBUS (sampling ranged from surface down to 230–600 m) and 7 stations in the sBUS (sampling ranged from surface down to 500–750 m). Furthermore, some squids were caught using hook and line in the upper two meters of the water column at 2 stations in the nBUS (ranging from 20 to 115 min per station, 4–5 rods) and 4 stations in the sBUS (ranging from 45 to 105 min per station, 4–6 rods). At 1 station in sBUS one squid was retrieved from a neuston catamaran haul (NCAT) used to sample the surface layer (0–20 cm sampling depth). Dorsal mantle length (DML) of each specimen was measured to the nearest mm below. This data set contains the results of the fatty acid trophic marker analyses of squid mantle muscle and midgut gland (MGG) tissue of 84 specimens. A modified carnivory index after Bode et al. (2015) was determined and ranged from 0.55 to 0.92. Differences in fatty acid compositions displayed distinct clusters separating squid families and different prey taxa through principal component analyses.